Bilum: A Cultural Object of the Pagan Melanau - Yakup Mohd. Rafee, Mohd. Rafee; Awangko Hamdan, Awang Arshad; Hishamuddin, Siri; Abdul Riezal, Dim; Mohd. Jefri, Samaroon (Medwell Publishing, 2017)
Bilum is among the endangered cultural objects and is used as a healing tool by the Pagan Melanau community, especially in Mukah and Dalat, Sarawak. Yet despite its central role in the community only relatively recently that researchers started taking serious notice of it with studies dating back to the 1960’s and 1970’s. Thus, this study provides an overview of the study on bilum in the Melanau community and its current state particularly with regard to its ritual practice and production. The discussion includes the general types of bilum, the bilum’s carver, spirit, ritual practices and production methods of the bilum. The findings were obtained through visual ethnographic methods to assess the effectiveness of visual analysis in ethnographic research and study the relationship between behavior and visual observation at the study site. The study concludes with the evolution of bilum over time and its impact on the Melanau community in the modern world.